O myśleniu statystycznym w pedagogice. Na marginesie odczytań książki Wiesława Szymczaka pt. Praktyka wnioskowania statystycznego - Pasikowski, Sławomir (Rocznik Pedagogiczny, 2020)
The article is devoted to the issue of statistical thinking in pedagogy and research conducted in this discipline. Inspired by the readings of the book by Wiesław Szymczak, The Practice of Statistical Inference, it contains comments on popular associations and misunderstandings about what statistics is, what its principles and goals are, and therefore also comments on the using of statistical methods inconsistently with the underlying assumptions of statistical theory.